Large or small? Rethinking China s forest bioenergy policies - Kahrl F; Su Y; Tennigkeit, Timm; Yang Y; Xu, Jianchu (Elsevier, 2013)
China s forest bioenergy policies are evolving against the backdrop of pressing national energy challenges similar to those faced by OECD countries, and chronic rural energy challenges more characteristic of developing countries. Modern forest bioenergy could contribute to solutions to both of these challenges. However, because of limitations in current technologies and institutions, significant policy and resource commitments would be required to make breakthroughs in either commercializing forest bioenergy or modernizing rural energy systems in China. Given the potential attention, funding, and resource trade-offs between these two goals, we provide an argument for why the focus of China s forest bioenergy policy should initially be on addressing rural energy challenges. The paper concludes with a discussion on strategies for laying the groundwork for a modern, biomass-based energy infrastructure in rural China.